2019
DOI: 10.1136/bmjopen-2018-024248
|View full text |Cite|
|
Sign up to set email alerts
|

Multilevel model of stigma and barriers to cancer palliative care in India: a qualitative study

Abstract: IntroductionPalliative care coverage and opioid consumption in India are relatively low compared with global data. The literature suggests commonplace concealment and collusion in withholding information, but these hypotheses lack evidence.ObjectivesThis study aimed to develop an explanatory evidence-based model of stigma, communication and access to cancer palliative care in India that can be used to develop, test and implement future interventions.DesignThis cross-sectional qualitative study sampled advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…The 29 studies identified included 8 quantitative studies, [25][26][27][28][29][30][31][32] 18 qualitative studies, [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] and 3 mixed-methods studies. [52][53][54] The sample size ranged from 10 participants to 313 participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 29 studies identified included 8 quantitative studies, [25][26][27][28][29][30][31][32] 18 qualitative studies, [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] and 3 mixed-methods studies. [52][53][54] The sample size ranged from 10 participants to 313 participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seven studies examined the barriers to PC utilization related to persons with cancer and their family. 29,30,35,40,42,49,50 The most common patient-related barriers included negative images/ stereotyping of PC, denial of the terminal nature of the disease/unrealistic expectations, and economic/logistic barriers. These are discussed below.…”
Section: Barriers Related To the Patient And The Familymentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 62 , 63 On the other hand, family involvement during the illness can result in collusion, selective sharing of information with the patient, and nondisclosure of the diagnosis which may hinder patients' well‐being. 1 , 64 , 65 Through their study in South India, Harding, Nair, and Ekstrand 66 reported the long‐lasting impact of cancer nondisclosure to the family in terms of lost employment and increased debts due to medical costs. The authors highlight families' lost opportunities to talk about their patient's psychological and spiritual needs due to collusion, * suggesting suboptimal use of healthcare services and family support.…”
Section: A Case For the Qpl In The Indian Oncology Settingmentioning
confidence: 99%
“…5 Palliative care is a global human right, to be provided 'throughout the illness course'. 6 According to Obadan-Udoh et al "providing care that is patient-centered is an indication of quality and that should be our ultimate goal. Dental profession has huge challenges in meeting these expectations."…”
mentioning
confidence: 99%